(untitled) (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
The article discusses the rapid development of automated medical information systems (AMIS) in the healthcare sector, emphasizing their importance for optimizing services in health care institutions (HCI). The article discusses trends in the implementation of AMIS aimed at reducing queues, increasing throughput, reducing costs and improving the quality of medical services. It also focuses on the need to integrate systems with state information bases and standardize electronic medical records (EMR).